Correction to: Multifactorial pathways in burn injury-induced chronic pain: novel targets and their pharmacological modulation (Molecular Biology Reports, (2022), 10.1007/s11033-022-07748-9) - Roy T.K.; Uniyal A.; Akhilesh; Tiwari V. (My University, 2025)
Unfortunately, the author names in the article that was published online are inaccurate; this error has been fixed with this correction. The original article has been corrected. © Springer Nature B.V. 2022.